Selection and heritability in the prediction of genetic gain in yellow passion fruit - Gonçalves, Gustavo Menezes; Viana, Alexandre Pio; Neto, Francisco Valdevino Bezerra; Pereira, Messias Gonzaga; Pereira, Telma Nair Santana (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this research was to evaluate the alternatives of selection for a population of yellow passion fruit, structured in Design I, for obtaining the best genotypic gain prediction. Six traits were evaluated in 113 progenies at two environments: Viçosa, MG, and Miracema, RJ, in Brazil, grouped in three sets in the randomized blocks design, with three replications and three plants per plot. For gain prediction calculation, the indexes of Mulamba & Mock, Pesek & Baker, Smith and Hazel, and the selection based on number of fruits per plants, were used. The absence of interaction genotype versus environment was observed. The alternatives that presented the best genetic gain prediction were the combined selection and selection among male families. Genetic gain prediction, based on combined selection, was 18.55% for direct selection of fruit number per plant. The indexes of Smith and Hazel presented the lowest genetic gain prediction. The indexes of Mulamba & Mock and Pesek & Baker had the highest predicted genetic gain. The indexes allied with alternatives studied have high potential in the selection of the progenies.